Demographic predictors of family relationships during adolescence - Borhan, Lihanna (Pearson, 2012)
The family is a very important milieu in a person’s development. It provides not only material and financial support but also the social and emotional support that is imperative to a person’s growth. Bronfenbrenner’s (1993) ecological systems theory placed the family as one of the elements in the microsystem. The microsystem is a very important layer of the developmental influence because of its direct relationship with the person. The elements in the microsystem provide activities, social roles and interpersonal relations to the developing person. And in cultures around the world, the family is a major sphere of influence in a person’s development.